The Effect of the Teams Game Tournament Learning Mode Assisted by Quizz Paper Mode on High Order Thinking Skills and Learning Outcomes in the Subject of Science in Grade V Elementary School - Suci Kurnia; Maria Montessori; Muhammadi; Ulfia Rahmi (Postgraduate, University of Mataram, 2025)
This research is motivated by the low HOTS and learning outcomes of students in science learning. The purpose of this study is to determine the effect of the Teams Game Tournament (TGT) learning model on HOTS and Learning Outcomes of fifth grade elementary school. This study uses a quantitative approach with a quasi-experimental method (quasi-experimental design) and a pre-action and post-action design. The results of the study show that: the t test is known to be tcount 1857> ttable 3160 and the sig. value. (2-tailed) <0.05. on significant differences between students who learn using the Teams Game Tournament (TGT) learning model and students who learn with conventional models on HOTS in science learning in fifth grade elementary school; the t test is known to be tcount 4.838> ttable 3.160 and the sig. value. (2-tailed) <0.05. there is a significant difference between students who learn using the Teams Game Tournament (TGT) learning model and students who learn with conventional models on student learning outcomes in science learning in grade V of elementary school; Manova test shows a sig. (2-tailed) value <0.05. there is a significant difference simultaneously or simultaneously between students who learn using the Teams Game Tournament learning model and students who learn with conventional models on HOTS and science learning outcomes in grade V of elementary school. Thus, it can be concluded that the Teams Game Tournament (TGT) learning model has a significant and effective effect in improving HOTS and learning outcomes.